ALICE IS NOT MISSING WONDERLAND - THE EASTWARD ENLARGEMENT OF THE EUROPEAN UNION - Prokopijević, Miroslav (Economic Annals, 2005)
In this paper I will try to show that the EU enlargement from 2004 is not a good economnic move for eight newcomers from Central and Eastern Europe (CEECs). It is unlikely that newcomers will get larger FDI, speed up their economic growth and catch up with richer EU countries, although this was broadly advertised both academically and by the EU “propaganda for happiness.” The EU subsidies, intended to offset accession costs, turn out to be useless if not damaging for acceding economies, because they change the structure of incentives. So, instead of being rewarded for accession, accession countries are going to be punished twice. Firstly, by lower FDI and a persisting GDP gap. Secondly, by getting subsidies which worsen the situation. CEECs would be better offstaying outside the EU and continuing to irnprove economic freedom and the rule of law. But even after they have acceded, there is still some space for reasonable objectives of the CEECs, due to unintended consequences of the socialist enlargement design.